Aspectos da reprodução e alimentação de Neoplecostomus microps (Loricariidae, Neoplecostominae) na microbacia do Ribeirão Grande, serra da Mantiqueira oriental (Estado de São Paulo) - Braga, Francisco Manoel de Souza [UNESP]; Gomiero, Leandro Muller; Souza, Ursulla Pereira (Universidade Estadual de Maringa, 2008)
Reproduction and feeding aspects of Neoplecostomus microps (Loricariidae, Neoplecostominae) in the Ribeirao Grande system, eastern Serra da Mantiqueira (São Paulo State). The Ribeirao Grande system is located in the slope of the Serra da Mantiqueira and is surrounded by Atlantic forest. Eight sites were surveyed in the Ribeirao Grande system, during the winter (July 2001), spring (October 2001), summer (February 2002) and fall (April 2002). Samples were made with an electrofishing device. Gonad maturation, levels of stomach fullness and fat content were analyzed and their distributions reported in an annual cycle. Neoplecostomus microps has a spawning in the spring through to summer. The size at sexual maturity is about 5.9 cm total length for males and 6.9 cm for females. The high values in October and February by the gonadosomatic index and the relative condition factor coincided with the spawning period. In the diet of N. microps were found Diptera larvae (Simulium, Chironomus), Plecoptera nymphs and Coleoptera aquatic Larvae (Psephenus). The increased feeding from summer to fall provided fat accumulation. During subsequent seasons, fish may utilize visceral fat reserves for maintenance and reproduction. The reproductive pattern and feeding are interpreted as being an adaptation with respect to temporal and spatial variation and food availability.
Reproduction and feeding aspects of Neoplecostomus microps (Loricariidae, Neoplecostominae) in the Ribeirao Grande system, eastern Serra da Mantiqueira (São Paulo State).